Current Challenges in Prostate Cancer Management and the Rationale behind Targeted Focal Therapy. (10th May 2012) - Barqawi, Al B.; Krughoff, Kevin J.; Eid, Khadijah
Abstract : Among men, prostate cancer has a high prevalence, with relatively lower cancer-specific mortality risk compared to lung and colon cancer. Prostate-specific antigen (PSA) screening has increased prostate cancer awareness since its implementation as a screening tool almost 25 years ago, but, due to the largely indolent course of this disease and the unspecific nature of the PSA test, increased incidence has largely been associated with cancers that would not go on to cause death (clinically insignificant), leading to an overdiagnosis challenge and an ensuing overtreatment consequences. The overtreatment problem is exacerbated by the high risk of side effects that current treatment techniques have, putting patients' quality of life at risk with little or no survival benefit. The goals of this paper are to evaluate the rise, prevalence, and impact of the overdiagnosis and ensuing overtreatment problems, as well as highlight potential solutions. In this effort, a review of major epidemiological and screening studies, cancer statistics from the advent of prostate-specific antigen screening to the present, and reports on patient concerns and treatment outcomes was conducted to present the dominant factors that underlie current challenges in prostate cancer treatment and illuminate potential solutions.